2016
DOI: 10.3390/ijms17101768
|View full text |Cite
|
Sign up to set email alerts
|

Seeking for Non-Zinc-Binding MMP-2 Inhibitors: Synthesis, Biological Evaluation and Molecular Modelling Studies

Abstract: Matrix metalloproteinases (MMPs) are an important family of zinc-containing enzymes with a central role in many physiological and pathological processes. Although several MMP inhibitors have been synthesized over the years, none reached the market because of off-target effects, due to the presence of a zinc binding group in the inhibitor structure. To overcome this problem non-zinc-binding inhibitors (NZIs) have been recently designed. In a previous article, a virtual screening campaign identified some hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…To investigate the BMMPI-binding mechanism, molecular-docking studies were performed on the MMP-2, MMP-8, MMP-9, and MMP-13 catalytic sites. 3D structures used for this study were selected through crossdocking studies, as previously reported [32]. Water molecules surrounding the bisphosphonic function in the experimental structures were maintained in the docking simulations in order to allow for water-mediated interactions of the zinc-binding group with the protein [33].…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the BMMPI-binding mechanism, molecular-docking studies were performed on the MMP-2, MMP-8, MMP-9, and MMP-13 catalytic sites. 3D structures used for this study were selected through crossdocking studies, as previously reported [32]. Water molecules surrounding the bisphosphonic function in the experimental structures were maintained in the docking simulations in order to allow for water-mediated interactions of the zinc-binding group with the protein [33].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty compounds were selected for purchase and the subsequent enzymatic assay. The selected compounds were not similar to the published non-zinc binding MMP-2 inhibitors [28][29][30][31][32].…”
Section: Visual Inspection and Final Selection Of The Hits For Purchasementioning
confidence: 86%
“…Currently, ~500 papers investigating the role of MMP inhibition in myocardial ischemia are available from the last 2 decades in PubMed database. There are several papers that describe the non-zinc binding, allosteric (e.g., π-π stacking) interactions of MMP-2 with selected inhibitors (Di Pizio et al, 2013 ; Agamennone et al, 2016 ; Ammazzalorso et al, 2016 ; Adhikari et al, 2018 ). Most of these papers employ MMP-2 as a potential biomarker for ischemic heart diseases or as a therapeutic target to evoke cardioprotection.…”
Section: Discussionmentioning
confidence: 99%